2019
DOI: 10.1159/000500188
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness of Cognitive Behavioral Therapy in Routine Outpatient Care: A 5- to 20-Year Follow-Up Study

Abstract: <b><i>Objective:</i></b> Long-term follow-ups several years after receiving cognitive behavioral therapy (CBT) are scarce and most of the existing literature describes follow-up data of randomized-controlled trials. Thus, very little is known about the long-term effects of CBT in routine care. <b><i>Methods:</i></b> We investigated psychological functioning in a sample of 263 former outpatients who had received CBT for a variety of mental disorders such as depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…Promoting lifestyle modifications and pursuit of psychological wellbeing, whose importance is increas ingly recognized in clinical medicine [316] and psychiatry [317], may provide more enduring effects. Psychothera peutic strategies aimed at improving coping with stressful situations [304,[318][319][320] may also be of value. The clinical diagnosis of allostatic overload may be helpful in a com prehensive approach that seeks to understand how the in teractions among genetics, mind, body, behavior and the environment affect both the risk of disease and the re sponse to treatment [321].…”
Section: Discussionmentioning
confidence: 99%
“…Promoting lifestyle modifications and pursuit of psychological wellbeing, whose importance is increas ingly recognized in clinical medicine [316] and psychiatry [317], may provide more enduring effects. Psychothera peutic strategies aimed at improving coping with stressful situations [304,[318][319][320] may also be of value. The clinical diagnosis of allostatic overload may be helpful in a com prehensive approach that seeks to understand how the in teractions among genetics, mind, body, behavior and the environment affect both the risk of disease and the re sponse to treatment [321].…”
Section: Discussionmentioning
confidence: 99%
“…The present trial involved the choice between PCT and PFPP, as representatives of CBT and PDT, because CBT and PDT are the 2 most widely used approaches in routine care facilities throughout Sweden, and because they draw upon distinct theories of change and ways of working. A different set of findings may have emerged had we chosen 2 other forms of psychotherapy, or indeed different forms of CBT [36] and PDT (however, there are no other panic-specific forms of PDT). It is also important to point out that the findings from this paper are based on mean scores for groups and there are likely important variations in outcomes for individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Some have found that good results can also be achieved following group CBT [6], and this format may be more cost effective and feasible in the clinical setting. Nevertheless, the number of studies, especially long-term studies (> 2 years), on CBT in groups is scarce [5,[7][8][9][10][11][12][13][14]. Long term outcome following CBT varies across studies.…”
Section: Introductionmentioning
confidence: 99%